Professional Nurse Traineeship. - Beatty, Ellen (1988)
Keywords: dept.nur; faculty_collection; sabbatical_report

Community Health Nursing. - Milone-Nuzzo, Paula (1988)
Keywords: dept.nur; faculty_collection; sabbatical_report

Workplace Health Promotion in a Sample of New York State Small Businesses: A Description of Current Programs and Associated Organizational Factors - Vicenzi, Angela E. (University Microfilms International, 1984)
Keywords: Health promotion; dept.nur; faculty_collection

Interleukin-1 induces time-dependent potentiation in isolated rat islets: Possible involvement of phosphoinositide hydrolysis - Zawalich, W.S.; Dierolf, B.; Zawalich, K.C. (Endocrinology, 1989)
Prior exposure of isolated perifused rat islets to the monokine interleukin-1 (IL-1) amplifies their subsequent insulin secretory response to 10 mM glucose. This potentiating effect of the monokine is dose dependent, lasts for at least 45 min after IL-1 removal from the medium, and is not confined to glucose; IL-1 also potentiates the insulin secretory responses to tolbutamide and glyceraldehyde. IL-1 exposure of islets incubated with myo-[2â€ 3H]inositol to label their phosphoinositides (PI) results in an increase in [3H]inositol efflux, an event that persists long after removal of IL-1 from the medium. Direct measurements of labeled inositol phosphate accumulation substantiate the concept that this sustained [3H] inositol efflux response is the direct result of a sustained increase in PI hydrolysis. These results expand the list of compounds that induce time-dependent potentiation in islets to include IL-1. This action of the monokine, mediated at least in part by Pi-derived second messenger molecules, may contribute to its postulated effects on insulin and glucose homeostasis. © 1989 by The Endocrine Society.
Keywords: Animal; Hydrolysis; In Vitro; Inositol Phosphates; Insulin; Interleukin-1; Islets of Langerhans; Kinetics; Male; Phosphatidylinositols; Rats; Rats, Inbred Strains; Reference Values; Support, Non-U.S. Gov't; Time Factors; animal cell; controlled study; dept.nur; insulin; interleukin 1; male; nonhuman; pancreas islet; phosphatidylinositide; priority journal; radioisotope; rat; tolbutamide; ⚠️ Invalid DOI

High-technology and hospice home care. Strange bedfellows - Hays, J.C. (Nursing Clinics of North America, 1988)
Technologic advances are changing hospice home care. A case study explores the clinical dilemmas and illustrates the educational and research agendas required to resolve them.
Keywords: Adult; Case Report; Female; Home Care Services; Hospices; Human; Patient Care Planning; Patient Care Team; Technology, High-Cost; Terminal Care; United States; computer analysis; dept.nur; home care; hospice; medical technology; organization and management; review; technical aid; united states; ⛔ No DOI found

Hospice policy and patterns of care - Hays, Judith C (Journal of Nursing Scholarship, 1986)
Hospice providers and policy makers are currently evaluating the emerging patterns of hospice care, especially regarding cost containment considerations. This study compared patterns of care for two groups of hospice homecare clients–one group, which received only homecare services for the duration of the hospice career; the other, which received both hospice homecare and inpatient services. The groups were significantly different on clinical parameters, number of homecare episodes, survival rate, and place of death. The impact of policy structures on continuity of care and service equity are discussed. Copyright © 1986, Wiley Blackwell. All rights reserved
Keywords: Aged; Comparative Study; Connecticut; Cost Control; Female; Home Care Services; Hospices; Hospitalization; Human; Male; Middle Age; Public Policy; United States; adult; aged; article; comparative study; cost control; dept.nur; economics; female; home care; hospice; hospitalization; human; male; organization and management; policy; utilization review